2021
DOI: 10.1002/sim.9098
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal Bayesian LASSO

Abstract: A reciprocal LASSO (rLASSO) regularization employs a decreasing penalty function as opposed to conventional penalization approaches that use increasing penalties on the coefficients, leading to stronger parsimony and superior model selection relative to traditional shrinkage methods. Here we consider a fully Bayesian formulation of the rLASSO problem, which is based on the observation that the rLASSO estimate for linear regression parameters can be interpreted as a Bayesian posterior mode estimate when the reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…However, previous evidence has confirmed that stepwise selection could generate the risk of model overfitting [ 50 ]. Modern statistical methods, such as bootstrapping or the least absolute shrinkage and selection operator, are promising methods for identifying important variables to resolve the overfitting problem [ 51 , 52 ]. Therefore, future studies should restrict the candidate list and adopt the shrinkage method to develop high-quality prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous evidence has confirmed that stepwise selection could generate the risk of model overfitting [ 50 ]. Modern statistical methods, such as bootstrapping or the least absolute shrinkage and selection operator, are promising methods for identifying important variables to resolve the overfitting problem [ 51 , 52 ]. Therefore, future studies should restrict the candidate list and adopt the shrinkage method to develop high-quality prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…The researcher [11] Mallick and others proposed in the year 2021 a proposal to represent the previous (prior) distribution of the parameter β, as this proposal assumed that the inverse Laplace distribution of the parameter β can be represented as follows:…”
Section: Iii3 Binary Reciprocal Lasso Quantile Regressionmentioning
confidence: 99%
“…Where it can be said that the relationship (3)(4)(5)(6)(7)(8)(9)(10)(11) produced the distribution of the variable λ to be .…”
Section: Iii5 the Full Conditional Posterior Distributionmentioning
confidence: 99%
“…Mallick et al (2021) and Zainab and Alhamzawi (2022), the above Bayesian hierarchical modelling produce an efficient Gibbs sampler that works as follows.…”
mentioning
confidence: 99%